ANALYSIS OF TRAINING AND DEVELOPMENT ON TEACHER PERFORMANCE AT NAMIRA ISLAMIC SCHOOL WITH JOB SATISFACTION AS MEDIATION - Britandy Dwika Suryabhuana; Prihatin Lumbanraja; Vivi Gusrini Rahmadani P (CV. Radja Publika, 2025)
This study aims to analyze the effect of training and development on teacher performance with job satisfaction as a mediating variable among teachers at Namira Islamic School Medan. The urgency of this research lies in the strategic role of teachers in improving education quality and the importance of continuous professional training to support optimal performance. This study employs an associative method with a quantitative approach. The population consists of 114 teachers, with 89 respondents selected as samples using proportionate stratified random sampling and Slovin's formula. The results indicate that training and development have a positive and significant impact on teacher performance. Furthermore, training and development positively influences teacher job satisfaction. Job satisfaction also shows a positive effect on improving teacher performance. Moreover, job satisfaction is proven to mediate the relationship between training and development and teacher performance. These findings highlight the importance of implementing well-structured and relevant training programs, as well as fostering a supportive work environment, to comprehensively enhance teacher performance.